Trends in Switching Coffee Consumption from Traditional Coffee Shops to Modern Cafés: A Push-Pull-Mooring Framework Perspective - Afiati, Lely; Misrah; Ardani, Edvi Gracia (Jurnal Aplikasi Manajemen, 2026)
The rapid growth of Indonesia’s coffee industry reflects changes in consumer behavior, where coffee consumption has become part of lifestyle and social interaction. The coexistence of traditional coffee shops and modern cafés in Semarang City has intensified competition and encouraged consumer switching behavior. This study examines the influence of push, pull, and mooring factors on consumers’ switching intentions using the Push–Pull–Mooring (PPM) framework. A quantitative survey was conducted with 150 consumers in Semarang City who had experience visiting both traditional coffee shops and modern cafés. Data were collected through online questionnaires and analyzed using Covariance-Based Structural Equation Modeling (CB-SEM). The results show that the push and pull effects positively and significantly influence consumers’ switching intentions from traditional coffee shops to modern cafés, whereas the mooring effect negatively and significantly influences these intentions. Dissatisfaction with traditional coffee shops and the attractiveness of modern cafés encourage consumers to switch, whereas emotional attachment, habitual behavior, familiarity, and switching costs restrain switching intention. The pull effect demonstrates the strongest influence among the examined variables. However, this study focuses on switching intention rather than actual switching behavior, as consumers may simultaneously consume coffee in both traditional coffee shops and modern cafés. This study extends the application of the PPM framework into an offline experiential consumption context and suggests that coffee businesses should strengthen emotional engagement and relationship-based strategies to sustain consumer loyalty in increasingly competitive coffee markets.